Traditional festivals in Vietnam - Đỗ, Phương Quỳnh (The gioi Publishers, 1995)
This book gives an account of a number of well-known festivals in the Plains of North VietNam (arranged in the order of Lunar months) in order to give a diversified picture of VietNam's traditional culture. In addition, the book also deals with a number of festivals of minority ethnic group for a very long time. The interactive cultural influence among these groups is not negligible